Rural Bangladeshi consumers’ willingness to pay for rice with improved nutrition via zinc biofortified rice and decreased milling practices - Herrington, Caitlin; Maredia, Mywish K.; Ortega, David L.; Taleon, Victor; Birol, Ekin; Sarkar, Md. Abdur Rouf; Rahaman, Md. Shajedur (International Association of Agricultural Economists, 2021)
Zinc deficiency is a severe public health issue in Bangladesh. We examine the effects of nutritional information on rural consumers’ willingness-to-pay (WTP) for two ways to address zinc deficiency—biofortification of rice with increased zinc content (an invisible trait) and low-milling that gives rice grains a distinctive light brown color (a visible trait) and sets it apart from the culturally preferred highlymilled white rice grain. Results of our economic experiments suggest that with nutritional information, consumers are willing to pay a premium of 6% for zinc biofortified rice compared to non-biofortified rice. However, results confirm the strong preference for high milled rice of Bangladeshi consumers who discounted less-milled rice by 14%. This discount was reduced to 10% with information, suggesting a positive effect (4%) of information on WTP for less-milled rice. We also find that consumers’ WTP for these two high-zinc rice grains was positively correlated with being a female, more education, and belonging to households with a major income source from non-farm activities and with children under five years of age. Results point to the importance of nutritional awareness campaigns for increasing zinc biofortified and low-milled rice consumption and guiding the targeting strategy for such campaigns.